Secagem por camada de espuma da polpa de frutos do cacaueiro (Theobroma cacao L.) adicionada de prebióticos - Freitas, Raimunda Valdenice da Silva (2022)
The objective of this work was to perform the foam layer drying of cocoa fruit pulp (Theobroma cacao L.) added with prebiotics. The development of the research consisted of steps included in Study I with an approach to the characterization of the raw material and drying of the cocoa pulp by layer of foam. In this step, cocoa pulp (blend 1) from the CCN51 and CEPEC 2005 genotypes was used, characterized through physical, physical-chemical and chemical analyses. The drying study of the raw material was carried out by the foam layer method with evaluations of the independent variables: concentration of the foaming agent (3, 4 and 5%); stirring time (4, 5 and 6 min) and drying temperature (50, 60 and 70 °C). Physical analyzes of the foams, kinetics of the drying processes and characterization of the powder products were carried out. In Study II, cocoa pulp (blend 2) from genotypes PS1319.2005 and PS1319.2006 was used as raw material. Different independent variables were evaluated, such as: drying temperature (50, 60 and 70 °C), concentration of the drying carrier agent: Maltodextrin (10, 15 and 20%) and emulsifying agent: Portogel or sparkling wine: juá bark powder (both in concentrations of 3, 4 and 5%). In view of the results obtained, the pulp (blend) was selected for drying by layer of foam added with prebiotics. In Study III, cocoa pulp (blend 2) was dried, added with different concentrations of the prebiotics Inulin and Fructo-oligosaccharides (0; 1.70; 5.85; 10 and 11.70%), physical characterization of the foams, evaluation of the powders obtained and as dependent variables: theoretical yield, drying time, moisture content, water activity, solubility and rehydration time of the powders. In Study IV and V, the physicochemical, technological, microstructural and functional properties of the selected powder were evaluated according to the results of the response variables analyzed in Study III. The cocoa pulp (blend 1) had high moisture content (85.71%), low titratable acidity (0.63g/100g), soluble solids content of 20.13 °Brix and the presence of micronutrients and macronutrients. In the foam layer drying process, the juá bark powder plays an important role in foam formation under conditions of higher concentration (5%), stirring time of 6 min and lower drying temperature (50 °C). For blend 2 drying, ideal conditions were established with 15% maltodextrin, 5% portogel and 8 min of agitation. The powder samples added with prebiotics and drying carrier agent showed satisfactory results for apparent density (0.296 g/mL and 0.262 g/mL), compacted density (0.330 g/mL and 0.273 g/mL) and absolute density (1.266 g/mL and 0.123 g/mL). The microstructure analysis indicated particles with variations in size and shape, porous and pointed appearance. The fresh pulp samples showed potential for use in the development of food products, expressive results for the content of soluble solids, sugars and low caloric value, and can be added to diets, food supplementation and technological processing. The use of cocoa pulp shows aggregation of value to this by-product with the production of potentially functional powder and available for longer periods for commercialization.